Perceived Stress due to COVID-19 Pandemic Among Employed Professional Teachers - Ryan Michael Oducado; Judith Rabacal; Rome Moralista; Khen Tamdang (International Journal of Educational Research and Innovation, 2021)
The unexpected occurrence of the COVID-19 outbreak has undeniably disrupted the normalcy of life. Stress has become an important concern in education since the COVID-19 outbreak. This descriptive-correlational online survey administered in August 2020 utilized the COVID-19 Perceived Stress Scale (COVID-19 PSS-10) to assess the COVID-19 perceived stress among employed Filipino teachers. Whitney U and Kruskal–Wallis tested for differences while Spearman's rho was used to analyze the correlation between variables. Results demonstrated that more than half of teachers experienced moderate COVID-19 stress. Females experienced significantly higher COVID-19 stress compared to males. A negative correlation was noted between self-rated health and COVID-19 stress while a positive correlation was found between the perceive risk of getting COVID-19 infection and COVID-19 stress. This study highlights that steps must be undertaken to help teachers deal with the stress of the COVID-19 crisis as well as they must be provided or taught with stress management interventions during this pandemic. This study could be used as a baseline for future research to assess the impact of COVID-19 stress among professional teachers. – – La aparición inesperada del brote de COVID-19 ha interrumpido sin lugar a dudas la normalidad de la vida. El estrés se ha convertido en una preocupación importante en la educación desde el brote de COVID-19. Esta encuesta en línea descriptiva-correlacional administrada en agosto de 2020 utilizó la Escala de estrés percibido COVID-19 (COVID-19 PSS-10) para evaluar el estrés percibido por COVID-19 entre los profesores filipinos empleados. Whitney U y Kruskal-Wallis probaron las diferencias mientras que la rho de Spearman se utilizó para analizar la correlación entre las variables. Los resultados demostraron que más de la mitad de los maestros experimentaron un estrés moderado por COVID-19. Las mujeres experimentaron un estrés por COVID-19 significativamente mayor en comparación con los hombres. Se observó una correlación negativa entre la salud autoevaluada y el estrés por COVID-19, mientras que se encontró una correlación positiva entre el riesgo percibido de contraer la infección por COVID-19 y el estrés por COVID-19. Este estudio destaca que se deben tomar medidas para ayudar a los maestros a lidiar con el estrés de la crisis de COVID-19, así como se les debe proporcionar o ense\~nar intervenciones de manejo del estrés durante esta pandemia. Este estudio podría usarse como base para futuras investigaciones para evaluar el impacto del estrés por COVID-19 entre los profesores profesionales.
Keywords: 330; COVID-19; corona virus; pandemic; mental health; stress; psychological well-being; teachers; educators